Reconfigurable coding acoustic meta-lens based on helical metamaterials - Li, Xiang; Li, Jian; Huang, Xinjing (Applied acoustics, 2023)
•We propose a 3D reconfigurable binary coding meta-lens (RCML) based on helical metamaterials for acoustic waves in the air.•We suggest a set of design and reconfiguration methods for RCML, which can modify the focus with small-scale adjustment.•The RCML has accurate focus point control ability and noticeable amplification effect. Acoustic lenses play an important role in acoustic sensing and imaging. We propose a reconfigurable coding meta-lens (RCML)based on helical metamaterials in the air. The proposed RCML consists of many reassemblable helical meta-units and tunnel-units that have stable phase-shift difference π; these two kinds of antiphase units are called logical “1{\Prime} and “0”. By specific array arrangement, the units “1” and “0” can form RCML with different discretization particle sizes. We suggest a set of design and reconfiguration methods for RCML, which can modify the focus via small-scale adjustment. Both simulations and experiments demonstrate that the RCML can realize acoustic convergence over a wide designed frequency band with a compact volume. For low-frequency acoustic waves, the thickness of the RCML is only 1/5.7 the wavelength. Moreover, RCML exhibit accurate focus point control and great amplification effect. Our study has great potential in versatile applications, including the design of acoustic sensors, energy collection devices and imaging systems.